School-Based Mental Health Initiative: Potentials and Challenges for Child and Adolescent Mental Health - Lai, Kelly Y. C.; Hung, Se-Fong; Lee, Hannah W. S.; Leung, Patrick W. L. (Frontiers in Psychiatry, 2022)
School-based mental health support services allow children and adolescents easy access to services without requirement of traveling to clinics and hospitals. We describe a School Mental Health Support Scheme (SMHSS) piloted in Hong Kong and discuss the challenges and learnings from the experience. This conceptual paper argues that accessibility is not the only advantage of such services. Teachers are significant others in child development, alongside with families. They play a central role in impacting the children’s/ adolescents’ needs for competence and adult attachment, while schools provide an expanded social network of peers for one’s social relationship. The fulfillment of these needs has powerful implications in the mental health of the children/adolescents. Teachers can help students to develop a sense of competence with self-worth and self-identity via providing guidance and feedback, whether they be on one’s strengths or weaknesses, with acceptance, tolerance and unconditional positive regard. Particularly, the latter define a form of teacher-student relationship or adult attachment that offers the children/adolescents emotional security and nourishment, protecting them from failings and adversities. Teachers can also supervise and guide their students’ social development with peers at schools. A recent meta-analysis has found preliminary evidence that those school-based mental health services integrated into the teachers’ routine teaching activities are more effective. Teachers, who are overworked and stressed by the schools’ overemphasis on academics and grades, have yet to fully grasp their unique roles in supporting students with mental health needs. This paper ends by advocating a paradigm shift in which both the healthcare professionals and educators should forge a mutually beneficial collaboration in jointly enhancing the mental health of children/adolescents at schools.